Abnormal Magnetoresistance Transport Properties of van der Waals Antiferromagnetic FeNbTe2 - Qi, Bao-tao; Guo, Jun-Jie; Miao, Ying-qing; Zhong, Mian-zeng; Li, Bo; Luo, Zi-yan; Wang, Xi-guang; Nie, Yao-zhuang; Xia, Qing-lin; Guo, Guang-hua (Frontiers in Physics, 2022)
The emergence of two-dimensional (2D) van der Waals magnetic materials has attracted enormous attention due to their novel physical phenomena and potential application in the fields of spintronics and information storage technology. Here, we systematically study the magnetic and transport properties of a van der Waals antiferromagnetic material, FeNbTe2. The magnetic and magnetoresistance measurements verified its antiferromagnetic properties, spin glass state, and negative magnetoresistance effect at lower temperatures. In addition, the measurement results of transport also show the existence of angle-dependent anisotropic magnetoresistance in a wide temperature range and anisotropic magnetoresistance inversion in a certain temperature range.